(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. Currently, war fatigue is one of the leading characteristics of the psychological and emotional state of Ukrainians. War, as a destructive phenomenon, has given rise to a new phenomenon for scientific understanding, known as war fatigue syndrome. The aim of this research is to theoretically explore the essence of the concept of "war fatigue syndrome" and to identify the psychological features of experiencing it.Methods. The research employs the following theoretical methods: analysis and synthesis, deduction and induction, comparison, systematization, and generalization of scientific sources related to the outlined problem.Results. The essence of the concept of war fatigue syndrome has been defined as a combination of physiological and psychological symptoms resulting from a sustained loss of personal resources due to prolonged and intense wartime events. Symptoms of this syndrome have been systematized. Major physiological symptoms include: chronic fatigue, deteriorating health, nervous agitation, sleep difficulties, headaches, breathing difficulties, decreased immunity, and others. Major psychological symptoms include: cognitive (slowed thought processes, negative thoughts, loss of life meaning, re-evaluation of values, depersonalization, etc.); emotional (despair, hopelessness, disappointment, stress, anxiety, apathy, aggression, negative emotions, compassion fatigue, frustration, guilt, ambivalent patriotic feelings, etc.); behavioral (reduced activity, productivity, loss of motivation, social isolation, avoidance of war topics, ignoring real threats, delayed life syndrome, substance abuse, etc.). The main determinants and sources of the development of this syndrome, as well as the main psychological defense mechanisms, have been identified.Conclusions. The features of experiencing war fatigue syndrome are determined by individual psychological traits, stress response patterns, and the specificity, frequency, and intensity of stressors.